DDX5 and DDX17—multifaceted proteins in the regulation of tumorigenesis and tumor progression - Xu, Kun; Sun, Shenghui; Yan, Mingjing; Cui, Ju; Yang, Yao; Li, Wenlin; Huang, Xiuqing; Dou, Lin; Chen, Beidong; Tang, Weiqing; Lan, Ming; Li, Jian; et al. (Frontiers in Oncology, 2022)
DEAD-box (DDX)5 and DDX17, which belong to the DEAD-box RNA helicase family, are nuclear and cytoplasmic shuttle proteins. These proteins are expressed in most tissues and cells and participate in the regulation of normal physiological functions; their abnormal expression is closely related to tumorigenesis and tumor progression. DDX5/DDX17 participate in almost all processes of RNA metabolism, such as the alternative splicing of mRNA, biogenesis of microRNAs (miRNAs) and ribosomes, degradation of mRNA, interaction with long noncoding RNAs (lncRNAs) and coregulation of transcriptional activity. Moreover, different posttranslational modifications, such as phosphorylation, acetylation, ubiquitination, and sumoylation, endow DDX5/DDX17 with different functions in tumorigenesis and tumor progression. Indeed, DDX5 and DDX17 also interact with multiple key tumor-promoting molecules and participate in tumorigenesis and tumor progression signaling pathways. When DDX5/DDX17 expression or their posttranslational modification is dysregulated, the normal cellular signaling network collapses, leading to many pathological states, including tumorigenesis and tumor development. This review mainly discusses the molecular structure features and biological functions of DDX5/DDX17 and their effects on tumorigenesis and tumor progression, as well as their potential clinical application for tumor treatment.